Pengaruh Terapi Relaksasi Benson dengan Perubahan Saturasi Oksigen pada Pasien TB Paru di Ruang Isolasi RSUD PROF. DR.ALOEI SABOE Kota Gorontalo - Nikmawati Puluhulawa; Fadli Syamsuddin; Mohamad Taufan Ibrahim; Alfandi Usman (Universitas Malahayati, 2024)
ABSTRACT Patients with Pulmonary Tuberculosis are often diagnosed with gas exchange abnormalities, leading to shortness of breath. An intervention that can be done to reduce shortness of breath in pulmonary TB patients is Benson relaxation focused on certain words or sentences repeatedly in a regular pattern. in this study, to determine the effect of Benson relaxation therapy on changes in oxygen saturation in pulmonary TB patients in the isolation room at Aloei Saboe Regional Hospital, Gorontalo City. Used in this research was pre-experimental with a one-group pre-post test design approach, with a sample of 15 pulmonary TB patients who experienced shortness of breath in the Isolation Room at Aloei Saboe Regional Hospital, Gorontalo City. Based on the results of statistical tests using the Wilcoxon test, a significant value or PV value was obtained, namely 0.000, which means 0.0000.05, so it can be concluded that Ha is accepted, which means that there is an effect of Benson relaxation therapy with changes in oxygen saturation in pulmonary TB patients in the Isolation Room at Aloei Saboe City Hospital Gorontalo. It is hoped that this will provide additional information to health workers at the Aloei Saboe Regional Hospital, Gorontalo City regarding the provision of Benson relaxation therapy to pulmonary TB patients who experience changes in oxygen saturation. Keywords: Benson Relaxation Therapy, Pulmonary TB, Oxygen Saturation ABSTRAK Pasien dengan Tuberkulosis Paru sering didiagnosis dengan kelainan pertukaran gas, yang menyebabkan sesak napas. Intervensi yang bisa dilakukan untuk mengurangi sesak pada pasien TB paru adalah relaksasi benson difokuskan pada kata atau kalimat tertentu yang berkali-kali dengan pola yang teratur. pada penelitian ini yaitu untuk mengetahui pengaruh terapi relaksasi Benson dengan perubahan saturasi oksigen pada pasien TB Paru di Ruang Isolasi RSUD Aloei Saboe Kota Gorontalo. Yang digunakan dalam penelitian ini adalah pra-eksperimental dengan pendekatan one-group pra-post test design, dengan sampel sebanyak 15 pasien TB Paru yang mengalami sesak nafas di Ruang Isolasi RSUD Aloei Saboe Kota Gorontalo. Berdasarkan hasil uji statistik menggunakan uji Wilcoxon didapatkan nilai signifikan atau nilai PValue yaitu 0,000 yang berarti 0,0000.05 sehingga dapat disimpulkan bahwa Ha diterima yang artinya terdapat pengaruh terapi relaksasi Benson dengan perubahan saturasi oksigen pada pasien TB Paru di Ruang Isolasi RSUD Aloei Saboe Kota Gorontalo. Diharapkan dapat menambah informasi kepada tenaga kesehatan yang berada di RSUD Aloei Saboe Kota Gorontalo tentang pemberian terapi relaksasi Benson pada pasien TB Paru yang mengalami perubahan saturasi oksigen. Kata Kunci: TB Paru, Terapi Relaksasi Benson, Saturasi Oksigen